2021
DOI: 10.3390/ijms22115874
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-1 Depletion Has a Differential Impact on Hyaluronic Acid Metabolism and Tumor Cell Behavior in Luminal and Triple-Negative Breast Cancer Cells

Abstract: Glycosaminoglycans (GAGs) and proteoglycans (PGs) are major components of the glycocalyx. The secreted GAG and CD44 ligand hyaluronic acid (HA), and the cell surface PG syndecan-1 (Sdc-1) modulate the expression and activity of cytokines, chemokines, growth factors, and adhesion molecules, acting as critical regulators of tumor cell behavior. Here, we studied the effect of Sdc-1 siRNA depletion and HA treatment on hallmark processes of cancer in breast cancer cell lines of different levels of aggressiveness. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Commonly, epithelial markers like CDH1 and CLDN are downregulated while mesenchymal markers such as FN‐1 and VIM are upregulated 22 . Previous studies in IBC cells had indicated downregulation of individual EMT markers such as CDH1, CLDN, VIM and snail upon Sdc‐1‐depletion, however, as both epithelial and mesenchymal markers were downregulated, the changes were not suggestive of a complete EMT 18,26,39 . In our DCIS model, Sdc‐1 knockdown was associated with an upregulation of the epithelial markers claudin and (moderately) E‐cadherin, of the mesenchymal marker fibronectin, and a modest downregulation of the mesenchymal marker vimentin (Figure 4).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Commonly, epithelial markers like CDH1 and CLDN are downregulated while mesenchymal markers such as FN‐1 and VIM are upregulated 22 . Previous studies in IBC cells had indicated downregulation of individual EMT markers such as CDH1, CLDN, VIM and snail upon Sdc‐1‐depletion, however, as both epithelial and mesenchymal markers were downregulated, the changes were not suggestive of a complete EMT 18,26,39 . In our DCIS model, Sdc‐1 knockdown was associated with an upregulation of the epithelial markers claudin and (moderately) E‐cadherin, of the mesenchymal marker fibronectin, and a modest downregulation of the mesenchymal marker vimentin (Figure 4).…”
Section: Discussionmentioning
confidence: 52%
“…22 Previous studies in IBC cells had indicated downregulation of individual EMT markers such as CDH1, CLDN, VIM and snail upon Sdc-1-depletion, however, as both epithelial and mesenchymal markers were downregulated, the changes were not suggestive of a complete EMT. 18,26,39 In our DCIS model, Sdc-1 knockdown was associated with an upregulation of the epithelial markers claudin and (moderately) E-cadherin, of the mesenchymal marker fibronectin, and a modest downregulation of the mesenchymal marker vimentin (Figure 4). Our results do not point towards a total EMT upon Sdc-1 knockdown but rather a partial EMT combined with ECM-interactions and deregulation of proteolysis.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Since we previously showed that heparan sulfate proteoglycans are capable of modulating breast and colon cancer stem cell properties, associated with therapeutic resistance [ 20 , 21 , 22 , 23 ], we evaluated the potential influence of SDC3 on the growth of three-dimensional spheroids as a readout of stem cell activity in a hanging drop assay [ 24 ]. Both SDC3-depleted and control siRNA-treated SKOV3 and CAOV3 cells formed dense spheroids after 4 days of culture that were surrounded by a margin of more loosely arranged cells ( Figure 2 A, left panel).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, overexpression of SDC1 resulted in increased angiogenesis promoters ( 66 ), including FGF2 and VEGF, and the anti-SDC1 antibody 46F2SIP was confirmed to effectively inhibit angiogenesis and induce vascular normalization ( 67 ). It was found that the reduction of SDC1 arrested cells from S phase to G1 phase, slowed cell cycle progression and inhibited cell proliferation ( 68 ). Therefore, SDC1 may be a suitable targeted therapeutic molecule for BRCA patients with various types.…”
Section: Discussionmentioning
confidence: 99%